Fabrication of piezoelectric thick films for development of micromechanical cantilevers - Kwon, Taeyun; Shin, Kyeong-Sik; Hyung, Minsurk; Eom, Kilho; Kim, Tae Song (KOREAN SOC MECHANICAL ENGINEERS, 2015)
We fabricated a piezoelectric thick film, whose electromechanical properties are optimized, for development of micromechanical cantilever as a sensor and actuator. Specifically, we studied the electromechanical properties of piezoelectric thick films made of different kinds of piezoelectric powders with their different sizes. The electromechanical properties of piezoelectric thick film are optimized when it is made of both micro- and nano-sized piezoelectric particles. Moreover, we fabricated a micromechanical cantilever using piezoelectric thick film, and investigated the vibrational characteristics of piezoelectric thick film-based microcantilevers. It is shown that a cantilever made of optimized piezoelectric thick film exhibits the excellent vibrational properties such as high Q-factor even in a viscous fluid, and that the resonance behavior of such a cantilever is very stable when compared with cantilevers made of other piezoelectric thick films. Our study provides the design rule of piezoelectric thick film for further development of micromechanical devices based on such a piezoelectric film.
Keywords: PZT; SILICON; DENSIFICATION; SENSORS